COMPARISON OF EFFICACY AND SAFETY PROFILE OF EMPAGLIFLOZIN AS A COMBINATION THERAPY IN OBESE TYPE 2 DIABETIC PATIENTS - Babar, Muhammad; Hussain, Mazhar; Ahmad, Manzur; Akhtar, Lubna (Journal of Ayub Medical College Abbottabad, 2021)
Background: Type 2 diabetes mellitus (T2DM) is a progressive disease due to multiple pathophysiological defects. Monotherapy alone cannot achieve adequate glycemic control and can lead to treatment failure. Empagliflozin, a sodium-glucose cotransporter2 (SGLT2) inhibitor improves glycemic control in patients with T2DM. There were limited studies to determine efficacy and safety profile of empagliflozin with conventional oral antidiabetic drugs (OADs) in Pakistan. So we investigated the efficacy and safety profile of empagliflozin as add-on therapy to metformin and sitagliptin in T2DM patients. Methods: In this comparative randomized placebo-controlled trial, 240 obese type 2 diabetic patients with inadequate glycaemic control (i.e, HbA1c’‰‰¥7%) with metformin and sitagliptin were allocated in to two groups. Patients in group B were given tab empagliflozin 10mg twice a day while patients in group A were given tab placebo for a period of 24 weeks. Changes in body weight, HbA1c, blood pressure were analysed pre and post treatment by using SPSS v23. Results: Empagliflozin caused a significant reduction in body weight -6.9±2.4 kg as compared to placebo -3.1±0.8 kg with p-value <0.001. This body weight reduction was further accompanied by reduction in systolic blood pressure -10.1±2.6 mmHg in empagliflozin group versus -5.3±2.5 mmHg in placebo group with p-value <0.001, and HbA1c -1.68±0.45 in empagliflozin group versus -0.1±0.06 in placebo group with p-value <0.001. There were 28.3% patients in empagliflozin group in whom HbA1c levels reduced <7% as compared to only 13.3% patients in placebo group (p-value 0.04). However no significant adverse effects were recorded in both study groups. Conclusion: Empagliflozin as a combination therapy has good efficacy and safety profile in obese type 2 diabetic patients.